PERLINDUNGAN KONSUMEN DALAM PERJANJIAN JUAL BELI ONLINE: (Studi Kasus Kebijakan Return Bukalapak) - Muhammad Fahad (JOURNAL SAINS STUDENT RESEARCH, 2023)
Buying and selling is an agreement to exchange objects or goods that have value voluntarily between two parties, one of whom receives the objects and the other party receives them in accordance with the agreement or conditions that have been justified by the sharia and agreed upon. According to Article 1457 of the Civil Code, a sale and purchase agreement is an agreement between a seller and a buyer in which the seller binds himself to hand over his ownership rights to an item to the buyer, and the buyer binds himself to pay the price of the item. Meanwhile, online buying and selling according to Alimin (2004:76) defines online buying and selling as a dynamic set of technology, applications and business processes that connect companies, consumers, certain communities through electronic transactions and trading of goods, services and information carried out electronically. And in online buying and selling, we must also regulate the protection of consumer rights in order to protect consumer rights, such as the product purchased is not the item that corresponds to the item purchased, this requires strict protection from the admin of the buying and selling site (open lapak) which is mostly in the application for opening a stall for goods does not match what the consumer purchased. This case is studied normatively and deepens the literature related to online buying and selling and consumer protection as well as deepening existing regulations.